Roma Mentor Project: The Roma Intellectual Friend Model - Bogdán Péter (Sciendo, 2023)
Introduction: The Roma Mentor Project has originally been the experimental educational model of Open Society Institute for multiply disadvantaged Roma and non-Roma youth in the period 2006-2013. Following the closure of OSI's experimental and alternative educational projects, it has been run further, during the 2016/17 academic year, with the support of the Norway Grant, by the Bhim Rao Association (located in Northern Hungary).